2015
DOI: 10.1007/s00784-015-1524-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of oral Candida colonization and its risk factors among patients with malignancies in China

Abstract: Old aged patients with pulmonary cancer and digestive tract malignant tumor are high-risk population for Candida colonization. Increasing frequency of teeth brush might be helpful for preventing Candida colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 47 publications
4
18
2
1
Order By: Relevance
“…Likewise, long‐term antibiotics use as a risk factor for Candida colonization is unclear (Fanello et al, ; Meurman et al, ). We did not find increased risk of Candida colonization in patients with history of antibiotics use as reported in a previous study in patients with cancer (Sun et al, ). This could be due to small numbers of subjects who took antibiotics in the month prior to this study.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Likewise, long‐term antibiotics use as a risk factor for Candida colonization is unclear (Fanello et al, ; Meurman et al, ). We did not find increased risk of Candida colonization in patients with history of antibiotics use as reported in a previous study in patients with cancer (Sun et al, ). This could be due to small numbers of subjects who took antibiotics in the month prior to this study.…”
Section: Discussionsupporting
confidence: 72%
“…The result is consistent with previous studies which reported 55%–100% Candida colonization in postradiotherapy cancer patients (de Freitas et al, ; Jain et al, ; Karbach et al, ; Thaweboon et al, ). The prevalence was considerably higher than previously reported 25.7%–55% Candida colonization in healthy population (Ergun et al, ; Lam‐Ubol et al, ; Meurman et al, ; Sun et al, ; Thanyasrisung et al, ).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This result could be explained by the fact that the patients in our study have more dental prosthesis; 59.4% of total patients had a dental prosthesis, while 75.7% patients who had Candida colonization had a dental prosthesis in our study. The contributing factors that facilitate Candida formation in dental prostheses are suggested as poor oral hygiene habits and insufficient cleaning of prosthesis and specifically natural affinity of the Candida strains to colonize on the acrylic material of the prosthesis . In our study, we could not find a relationship between oral hygiene and inflammation.…”
Section: Discussioncontrasting
confidence: 77%
“…C. albicans was the most common species isolated from patients, accounting for 30.8% in patients with pulmonary cancer (n=78), 33.7% in patients with digestive tract malignant tumor (n=101), and 12.7% in patients with hematopoietic system tumor (n=79). Cancer patients are a high-risk population for Candida colonization (10).…”
Section: Introductionmentioning
confidence: 99%